Reviewing smokeless tobacco epidemiology, carcinogenesis, and cessation strategy for otolaryngologists. (10th February 2018) - Stanisce, Luke; Levin, Kristin; Ahmad, Nadir; Koshkareva, Yekaterina
Abstract : Objectives/Objectives: We aimed to provide an otolaryngologist‐targeted summary regarding the epidemiology, carcinogenesis, and cessation strategies for smokeless tobacco usage. Study Design: Evidence‐based literature review. Methods: We reviewed the current evidence‐based literature concerning trends in smokeless tobacco use, associations with neoplastic change, and therapeutic interventions to assist with sustained abstinence. In complement, we present an actual case of laryngeal squamous cell carcinoma in the setting of chronic tobacco‐dentifrice usage in a lifelong nonsmoker. Results: This report provides a synopsis of epidemiological data and evidence‐based recommendations for general, pharmaceutical, and behavioral cessation strategies. Conclusions: Smokeless tobacco use continues to be prevalent among patients seen by otolaryngologists, particularly of various Indian and Southeast Asian descent. The data presented in this article will aid in the identification of at risk patients. The provided recommended cessation strategies will tool otolaryngologists for patient counseling and management, ultimately aimed at improving health outcomes. Laryngoscope, 128:2067–2071, 2018